The role of FDI in regional economic growth in Central & Eastern Europe: the case of the Hungarian regions - Zoltan Gal; Andras Gyimesi (Eastern Journal of European Studies, 2025)
FDI has been a key driver of economic transformation in Central and Eastern Europe (CEE). However, its long-term impact on GDP growth is limited, with benefits often concentrated in more developed regions, exacerbating regional disparities. This paper examines the relationship between FDI inflows, GDP growth, and gross fixed capital formation (GFCF) in Hungarian regions from 2000 to 2018 using panel econometric methods. Panel granger causality tests, and panel regression models (using first difference effect) are conducted controlling for GFCF, employment, R&D and the global financial crisis. Findings reveal that FDI does not significantly drive regional GDP growth, highlighting the importance of endogenous growth factors and local entrepreneurial ecosystems. The study critiques the FDI-led model, linking its shortcomings to economic nationalism and regional disintegration.